Be careful what you wish for-- - Stine, R. L. (New York : Scholastic, 1993)
The laughingstock of the girls' basketball team, klutzy Samantha Byrd is determined to pay back mean Judith Bellwood for making fun of her on the court, but she never expects her revenge to get out of hand.
"An Apple paperback."
4.
008-012.
570
Accelerated Reader AR
Keywords: Basketball stories; Sports stories; Horror tales; Wishes -- Fiction; Revenge -- Fiction; Basketball -- Fiction; Horror stories; Horror fiction